2009
DOI: 10.1111/j.1467-9922.2009.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning L2 German Vocabulary Through Reading: The Effect of Three Enhancement Techniques Compared

Abstract: This study investigated three techniques designed to increase the chances that second language (L2) readers look up and learn unfamiliar words during and after reading an L2 text. Participants in the study, 137 college students in Belgium (L1 = Dutch, L2 = German), were randomly assigned to one of four conditions, forming combinations of two between-subject factors: ± prereading test announcement and ± postreading vocabulary task. Comprehension questions were used to direct participants' attention to half of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
96
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 32 publications
10
96
0
4
Order By: Relevance
“…The extra contextual information provided by German feedback could therefore explain the tendency for implausible errors to be corrected more often on the delayed test by participants who received German feedback as compared with English feedback. Context could be beneficial in this case because it may provide another chance to infer the word's meaning (Nation, 2001), encourage elaborative processing of the word's meaning (e.g., Cheng & Good, 2009;Craik & Lockhart, 1972;Peters et al, 2009), or provide a greater variety of retrieval cues that can facilitate future recall of the word's meaning (e.g., Young & Bellezza, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extra contextual information provided by German feedback could therefore explain the tendency for implausible errors to be corrected more often on the delayed test by participants who received German feedback as compared with English feedback. Context could be beneficial in this case because it may provide another chance to infer the word's meaning (Nation, 2001), encourage elaborative processing of the word's meaning (e.g., Cheng & Good, 2009;Craik & Lockhart, 1972;Peters et al, 2009), or provide a greater variety of retrieval cues that can facilitate future recall of the word's meaning (e.g., Young & Bellezza, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…When the goal is comprehension, participants may not deliberately try to learn the meanings of unknown words (e.g., Hulstijn, Hollander, & Greidanus, 1996;Laufer, 2003). Indeed, some research has found that unknown words are more likely to be ignored when they are not relevant to comprehending the meaning of a passage (e.g., Hulstijn, 1993;Peters, Hulstijn, Sercu, & Lutjeharms, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that direct instruction techniques can significantly increase reading comprehension (Peters, Hulstijn, Sercu, & Lutjeharms, 2009). It was, however, found to be inadequate for fully preparing ESL/EFL learners (Nation & Waring, 1997).…”
Section: Vocabulary Learning Through Readingmentioning
confidence: 99%
“…Esta investigadora descubrió que el grupo de estudiantes que desarrolló ejercicios interactivos de vocabulario después de la lectura mejoró de manera significativa en comparación al grupo que solo leyó los textos. Estudios más recientes han confirmado los hallazgos de las investigaciones pioneras en L2, utilizando diversas actividades centradas en el vocabulario, tales como ejercicios de comprensión lectora, ejercicios de vocabulario contextualizados, compleción de palabras, entre otras (Kim, 2008;Min, 2008;Peters, Hulstijn, Sercu & Lutjeharms, 2009;Sonbul & Schmitt, 2010;Little & Kobayashi, 2011).…”
Section: Introductionunclassified